Intervenção educativa para adesão à terapia antirretroviral de crianças que vivem com HIV: estudo quase experimental - Ramos Junior, Angelo (2024)
Currently, according to studies published in Brazil, 99% of vertical transmissions can be prevented through ministerial actions. However, when these actions are ineffective and HIV infection occurs, it is necessary to develop technologies to care for these children living with HIV. The objective of this study was to evaluate the impact of an educational intervention in the form of a booklet for adherence to antiretroviral therapy for children living with HIV. This is a quasi-experimental, intervention-type study, and was composed of two groups. The so-called Intervention Group (IG) received the educational intervention in the form of a booklet and routine guidance from the service. The Routine Group (GR) received the guidance and care recommended by the institution, without the application of the educational booklet as an intervention. The Questionnaire for the Assessment of Adherence to Antiretroviral Treatment (CEAT - VHI, Portuguese version [Brazil]) was used to assess the impact of the technology. As a result of the study, it was found that, previously, 43.5% used antiretroviral medications because they felt better, increasing this percentage to 91.3% (p=0.001) after the educational intervention. Before, 52.2% took antiretroviral medications, increasing this percentage to 95.7% (p=0.003). They were asked if they had ever felt sad or depressed and stopped taking their medication, and it was found that previously, 43.5% had not stopped taking antiretroviral medications, but later this percentage increased to 87.0% (p=0.002). Another question was how much the child tried to continue with the treatment, and previously, 34.8% tried to follow the treatment, increasing this percentage to 78.3% (p=0.001) after the educational intervention. Regarding the improvement in health since starting to take HIV medication, it was found that 47.8% considered that their health had improved before, but this percentage increased to 82.6% later (p=0.005). In the item education, a statistically significant difference was observed between participants with complete elementary education in the intervention group. Statistical analyses indicated good levels of adherence after the intervention was implemented, a fact that reaffirms the importance of health education using technologies. Thus, the educational booklet used in conjunction with the service's routine guidelines promotes improved levels of knowledge and increases adherence to treatment for these children living with HIV. Reception, humanization of care and breaking the social stigma surrounding HIV infection are potential factors for good adherence to treatment.